Antiphospholipid antibody syndrome as a cause of inferior vena cava thrombosis (vol 46, pg 194, 2001) - Tütüncüler, F; Cihangiroglu, MM; Aydinoglu, AH; Aygün, AD (Turkish J Pediatrics, 2005)
[Abstract Not Available]